Knowledge, attitude, and awareness regarding dental implants in a Saudi subpopulation - Alshammari, Sultan T.; Alwajaan, Badreyah M.; Alshammari, Saad A.; Madfa, Ahmed A.; Albaqawi, Ahmed H. (International Journal Of Community Medicine And Public Health, 2022)
Background: The aim of the present study evaluated and elevated the knowledge, attitude and awareness of people life in Hail region to dental implants as option of treatment to replace the missing teeth. Methods: The present study was conducted in dental clinics in Hail region. Study sample was consisted of total 428 individuals. Individuals, who were meted the determined inclusion criteria in this study, will be selected for answer the structured questioners. Chi-square test to determine the significant differences of the study parameters Results: Among of participants, females were 161 (37.6%) and males were 267 (62.4%) of the participants. The subjects that heard about dental implants from internet was 126 (29.4%). Majority of the subjects 207 (48.4.2%) had a friend treated with an implant. Around 326 (76.2%) responders want to learn more about implants. Most of subjects 206 (48.1%) thought that dental implant require 6 months from the first examination until your prosthesis is finished. About of 148 (34.60) believed that survival rate will be life. Around 326 (76.2%) responders wished to get dental implants inserted from a specialist. Majority of the responders 281 (65.7%) thought implants required superior cleanliness and care and that it cannot be cleansed like natural dentition. Conclusions: Patients have little information and awareness regarding dental implants.